2021
DOI: 10.4103/jfmpc.jfmpc_1881_20
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with lower extremity amputation in Sudanese individuals with diabetes

Abstract: Background: Lower extremity amputation (LEA) in individuals with diabetes is a serious health issue with a considerable physical and social burden. The aim of this study was to assess the prevalence and risk factors associated with LEA in diabetic foot ulcer (DFU) patients. Materials and Methods: This was a cross-sectional health facility-based study that recruited 315 diabetes individuals with foot ulcers from the diabetes center in Khartoum, Sudan. Direct interviewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…To effectively reduce LEAs in LMICs, initiating improvements in primary care and emergency department practices is imperative. A study conducted in Sudan identified several risk factors for amputation among patients with DFUs, including hypertension, retinopathy, nephropathy, large ulcer sizes (>2.5 cm), and neuropathy 73 . The development of an updated risk stratification system utilizing these risk factors to inform management and treatment protocols is therefore essential to preventing LEAs.…”
Section: Future Strategies For Reducing Dfu‐related Amputations In Lmicsmentioning
confidence: 99%
“…To effectively reduce LEAs in LMICs, initiating improvements in primary care and emergency department practices is imperative. A study conducted in Sudan identified several risk factors for amputation among patients with DFUs, including hypertension, retinopathy, nephropathy, large ulcer sizes (>2.5 cm), and neuropathy 73 . The development of an updated risk stratification system utilizing these risk factors to inform management and treatment protocols is therefore essential to preventing LEAs.…”
Section: Future Strategies For Reducing Dfu‐related Amputations In Lmicsmentioning
confidence: 99%